Critical Review of Millennial Generation Involvement In Government: Opportunities And Challenges In Building Democracy In Indonesia - Mursito, Mursito; Wijayanti, Tutik; Irawan, Hendri; Pradanna, Satrio Alpen; Aba, Akbar (Universitas Negeri Semarang, 2024)
The millennial generation or the young generation plays a crucial role in building democracy in Indonesia because they have great potential to influence social and political changes in the future. According to a survey conducted by the Centre for Strategic and International Studies (CSIS), only 14.6% of young people are interested in the Legislative branch, and only 14.1% of young people aspire to run for regional leadership positions. Some issues faced by the young generation in government include a lack of interest in politics, limited access to political education, and the dominance of political elites in decision-making. As of now, a survey conducted by the Democracy Association has recorded the election of 20 young regional leaders and 17 young deputy regional leaders who are under 34 years old. This means that 13.7% of millennials are in positions of power, presenting both challenges and opportunities for Indonesian democracy. The research methodology employed in this article is a qualitative descriptive approach using literature study techniques, wherein the author collects relevant articles related to the research topic. This study will discuss the opportunities for the young generation to play a role in government and the challenges they face in their involvement, as they are seen as the nation's future successors capable of contributing to the development of the democratic Republic of Indonesia